Strategic Management in Action / Third Edition - Coulter Mary (Pearson - Prentice Hall, 2005)
This book presents current strategic management theories and practices in an engaging, lively and exciting format. Preface, Introducing the Concepts, The Context of Managing Strategically, Assessing Opportunities and Threats: Doing an External Analysis, Assessing Strengths and Weaknesses: Doing an External Analysis, Functional Strategies, Competitive Strategies, Corporate Strategies, Strategic Management in Other Organization Types, How to Do a Comprehensive Case Analysis, Comprehensive Cases for Analysis, Index.